130k views
5 votes
Choose the correct simplification of (5x − 6)(3x2 − 4x − 3).

2 Answers

5 votes
(15x^3 -38x^2 +9x+ 18) 
User Piotr Malec
by
6.4k points
5 votes

Answer:
15x^3-38x^2+9x+18

Explanation:

Given expression :
(5x-6)(3x^2- 4x-3)

Using distributive property,


a(b+c)=ab+ac\\\\or\ (b+c)a=ba+ca

Thus,
(5x-6)(3x^2- 4x-3)\\\\=(5x-6)3x^2-(5x-6)4x-(5x-6)3\\\\=5x(3x^2)-6(3x^2)-5x(4x)- (-6)(4x)-5x(3)-(-6)(3)\\\\=15x^3-18x^2-20x^2+24x-15x+18

Combining like terms we get


15x^3-18x^2-20x^2+24x-15x+18\\\\=15x^3-38x^2+9x+18

User Swyx
by
6.3k points